Comparison of ductile iron and seamless steel pipes for use in grouted sleeve splices under monotonic and cyclic loads. (15th July 2023) - Lu, Zhongyu; Gao, Shuai; Liu, Genghao; Lin, Jiaxiang; Zhu, Jingtao; Xie, Jianhe
Abstract: Ductile iron is often used for grouted sleeves due to its excellent toughness and ductility. Considering the greater cost of ductile iron, less expensive seamless steel has received much attention for use in grouted sleeves. This paper presents the results of an investigation of the tensile performance of grouted sleeve splices made of ductile iron and seamless steel pipe. Static tests and hysteretic tests were conducted for grouted sleeve splices with rebars. The various tested parameters included different types of grouted sleeve splices and diameters of rebar (12, 16, 20, and 22 mm). The splices with ductile iron showed better performance than those with seamless steel. The failure mode of all specimens was rebar rupture in the static test. The residual deformation was larger for the splices with the seamless steel pipe than those with ductile iron pipe. When the diameter of the rebar was 20 mm, the residual deformation of the splices with seamless steel pipe was three times that of the splices with ductile iron pipe, although their ultimate bearing capacities were similar. This indicated good interfacial bonding performance of the specimens of splices with ductile iron pipe. With cyclic loading, the splices with ductile iron pipe showed better capacities for energy dissipation and plastic deformation than the splices with seamless steel pipe. The maximum lateral displacement of the splices with seamless steel pipe was 1.2 times that of the specimens with ductile iron pipe, which can be attributed to the transverse cracks observed at the free end of the interface between the grouting material and rebar in the case of seamless steel pipe. Thus, grouted sleeves with seamless steel pipes were recommended for use under static conditions with no strict limitations on deformation. Highlights: A comparison of ductile iron and seamless steel pipes for use in grouted sleeve splices was studied. Grouted sleeve splices with ductile iron showed better performance under monotonic and cyclic loads. Application suggestions were proposed based on the test results.